Prospective Study Testing a Simplified Paclitaxel Premedication Regimen in Patients with Early Breast Cancer. (24th September 2021) - Barroso‐Sousa, Romualdo; Vaz‐Luis, Ines; Di Meglio, Antonio; Hu, Jiani; Li, Tianyu; Rees, Rebecca; Sinclair, Natalie; Milisits, Lindsey; Leone, Jose Pablo; Constantine, Michael; Faggen, Meredith; Briccetti, Frederick; et al.
Abstract: Background: In early trials, hypersensitivity reactions (HSRs) to paclitaxel were common, thus prompting the administration of antihistamines and corticosteroids before every paclitaxel dose. We tested the safety of omitting corticosteroids after cycle 2 during the paclitaxel portion of the dose‐dense (DD) doxorubicin‐cyclophosphamide (AC)–paclitaxel regimen. Patients, Materials, and Methods: In this prospective, single‐arm study, patients who completed four cycles of DD‐AC for stage I–III breast cancer received paclitaxel 175 mg/m 2 every 2 weeks for four cycles. Patients received a standard premedication protocol containing dexamethasone, diphenhydramine, and a histamine H2 blocker prior to the first two paclitaxel cycles. Dexamethasone was omitted in cycles three and four if there were no HSRs in previous cycles. We estimated the rate of grade 3–4 HSRs. Results: Among 127 patients enrolled, 125 received more than one dose of protocol therapy and are included in the analysis. Fourteen (11.2%; 90% confidence interval, 6.9%–20.0%) patients had any‐grade HSRs, for a total of 22 (4.5%; 3.1%–6.4%) HSRs over 486 paclitaxel cycles. Any‐grade HSRs occurred in 1.6% (0.3%–5.0%), 6.5% (3.3%–11.3%), 7.4% (3.9%–12.5%), and 2.6% (0.7%–6.6%) of patients after paclitaxel cycles 1, 2, 3, and 4, respectively. Dexamethasone use was decreased by 92.8% in cycles 3 and 4. Only one patient experienced grade 3 HSR in cycles 3 or 4, for a rate of grade 3/4 HSR 0.4% (0.02%–2.0%) (1/237 paclitaxel infusions). That patient had grade 2 HSR during cycle 2, and the subsequent grade 3 event occurred despite usual dexamethasone premedication. A sensitivity analysis restricted to patients not known to have received dexamethasone in cycles 3 and 4 found that any‐grade HSRs occurred in 2.7% (3/111; 0.7%–6.8%) and 0.9% (1/109; 0.05%–4.3%) of patients in cycle 3 and 4, respectively. Conclusion: Corticosteroid premedication can be safely omitted in cycles 3 and 4 of dose‐dense paclitaxel if HSRs are not observed during cycles 1 and 2. Implications for Practice: Because of the potential for hypersensitivity reactions (HSRs) to paclitaxel, corticosteroids are routinely prescribed prior to each dose, on an indefinite basis. This prospective study, including 125 patients treated with 486 paclitaxel cycles, demonstrates that corticosteroids can be safely omitted in future cycles if HSRs did not occur during cycles 1 and 2 of paclitaxel and that this strategy reduces the use of corticosteroids in cycles 3 and 4 by 92.8% relative to current standard of care. Abstract : To avoid hypersensitivity reactions, corticosteroids are routinely prescribed before each dose of paclitaxel. This article reports the results of a study that focused on whether corticosteroids could be safely omitted in later cycles of treatment if reactions did not occur during earlier cycles.